TERJEMAHAN TADHAFUL QOROIN AL-QUR’AN DEPARTEMEN AGAMA - Sri ana; Yufridal Fitri Nursalam (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2021)
The translation of the Koran for Muslims is a tool for understanding the Koran because the Qur'an is in Arabic. However, the process of translating from the Source language to the target language is certainly not easy, both linguistically and non-lunguistic. Tadafhur Qorain (pointer) which for the translator is very helpful in finding or revealing the appropriate meaning for the Source language and the Target language because it not only pays attention to the side of linguistic meaning but also non-Linguistic. In the translation of the Al-Qur'an owned by the Ministry of Religion, there are a variety of tadhafur used by the translators, including Qorinah Lafzhi, Aqli and context. So the better the translator's mastery of Tadhafur Qorain will make it easier to find the right meaning both to understand the source language and its correctness in Target language. Terjemahan Al-Qur'an bagi umat Islam menjadi alat untuk memahami Al-Qur'an karena Al- Qur'an berbahasa Arab. Namun proses penerjemahan dari bahasa sumber ke bahasa sasaran tentunnya tidak mudah, baik sisi linguistik dan non linguistik. Tadafhur Qorain (penunjuk) yang bagi penerjemah sangat membantu dalam mencari atau mengungkap makna yang sesuai untuk bahasa sumber dan bahasa sasaran, karena tidak hanya memperhatikan sisi makna linguistik tapi juga non-Linguistik. Di dalam terjemahan Al-Qur'an punya Depag terdapat ragam tadhafur yang dipakai oleh penerjemah diantaranya adalah qorinah Lafzhi, Aqli dan konteks.Jadi semakin baik penguasan penerjemah terhadap Tadhafur Qorain akan memudahkan dalam pencarian makna yang tepat baik untuk memahami bahasa sumber dan penepatan nya dalam bahasa Sasaran.